The Role of HR Analytics as a Moderator in the Integration Model of HR Capabilities and Strategic Alignment on the Sustainable Performance of Plantation Sector Companies in North Sumatra - Saidan Sany Lubis; Soulthan Saladin Batubara; Iskandar Muda (CERED Indonesia Institute, 2025)
This research seeks to examine the function of HR Analytics as a moderating variable in the integration model of HR Capabilities and Strategic Alignment concerning Sustainable Performance in plantation sector enterprises in North Sumatra. The study's background stems from the significance of the plantation sector as a primary contributor to the regional GRDP, despite encountering challenges in sustainability, digital readiness, and HR competencies. This study employed a quantitative methodology utilizing the PLS-SEM technique, involving 162 participants, including HR managers, plantation managers, departmental assistants, and sustainability officers. The results show that HR Capabilities don't have a big effect on Sustainable Performance, but Strategic Alignment does have a big negative effect. HR Analytics has a big effect on Sustainable Performance, but it doesn't change the link between HR Capabilities and performance. On the other hand, HR Analytics makes the link between Strategic Alignment and Sustainable Performance worse. These results show that HR digitalization and the use of analytics are important for plantation companies to make their business processes more flexible, efficient, and long-lasting.